Clinical performance of a novel sirolimus-coated balloon in coronary artery disease: EASTBOURNE registry. Issue 2 (February 2021) - Cortese, Bernardo; Testa, Luca; Di Palma, Gaetano; Heang, Tay M.; Bossi, Irene; Nuruddin, Amin A.; Ielasi, Alfonso; Tespili, Maurizio; Perez, Ignacio S.; Milazzo, Diego; Benincasa, Susanna; Latib, Azeem; et al.
Abstract : Aims: The purpose of the EASTBOURNE registry is to evaluate the immediate and long-term clinical performance of a novel sirolimus-coated balloon (SCB) in a real-world population of patients with coronary artery disease. We here present the prespecified interim analysis after the enrollment of the first 642 patients who obtained 1-year clinical follow-up. Methods: EASTBOURNE is a prospective, international, multicenter, all-comer investigator-driven clinical registry, which is enrolling consecutive patients treated with SCB at 42 European and Asiatic centers. Primary study endpoint is target-lesion revascularization (TLR) at 12 months. Secondary endpoints are procedural success and major adverse cardiac events through 36 months. Results: Diabetes mellitus was present in 41% of patients. Acute coronary syndrome was present in 45% of patients and de novo lesions were 55%; 83% of the in-stent restenosis (ISR) patients had drug-eluting stents restenosis. Lesion predilatation was performed in 95% of the cases and bailout stenting occurred in 7.5%. So far, 642 patients have a complete 12-month follow-up. TLR occurred in 2.5%, myocardial infarction in 2.3%, total death in 1% and major adverse cardiac events in 5.8% of patients. A prespecified analysis of comparison between ISR and de-novo lesions showed a significantly higher occurrence of TLR in the ISR population (5.4 vs. 0.2%, P  = 0.0008). Conclusion: The current interim analysis of 12-month follow-up of the EASTBOURNE registry shows good immediate performance and an adequate and encouraging safety profile through 12 months for this novel SCB.